RAPD AND ISSR ANALYSIS OF THE GENETIC RELATIONSHIP AMONG SOME SPECIES IN RUTACEAE IN AND APICEAE IN IRAQ. - & Ibraheam, Altameme (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Random amplified polymorphic DNA (RAPD) technique was used as a tool for assessing genetic diversity and species relationships among five species from Rutaceae family [Sour orange (Citrus aurantium L.); Sweet Orange (Citrus sinensis (L.) Osbeck); Mandarin (Citrus reticulata Blanco); Pummelo (Citrus maxima (Burm.) Merr.) and Grapefruit (Citrus paradisi Macf.)] and four species from Apiaceae [Carrots (Daucus carota L.; Celery (Apium graveolens (Mill.) Pers.); Parsley (Petroselinum crispum) and Dill (Anethum graveolus L.)]. These plants were collected from a different region at Hilla city in Iraq. A total of 50 polymorphic amplified products from 170 bands were obtained from eight primers (OPC2, OPC8, OPC14, OPB11, OPB18, BH10, BH11 and BH14) in Citrus species and the value of Jaccard’s coefficient ranged from 0.246 to 0.690. In contrast of 81 polymorphic amplified products from 129 bands in four species in Apiaceae and the value of Jaccard’s coefficient ranged from 0.080 to 0.269. Based on the bivariate (1-0) data and genetic similarity with the use of the UPGMA cluster method, the dendrogram separated the studied species. Therefore, it could be concluded that RAPD technique an efficient technique for studying the molecular characterization and used for resolving relationships among plant populations.